Two complete chloroplast genomes of Ceratophyllum, an aquatic genus with unresolved phylogenetic position - Shuangyan Ru; Zhigang Wu; Huijun Wang; Qi Li; Tao Li (Mitochondrial DNA. Part B. Resources)
Ceratophyllum is an aquatic genus noted for its enigmatic position in the angiosperm phylogenetic tree. In this study, we assembled and annotated the chloroplast genomes of two species. The chloroplast genome length of Ceratophyllum platyacanthum subsp. oryzetorum (Kom.) (V.Komarov, 1988) and Ceratophyllum submersum L. (Carl Linnaeus, 1763) is 156,168 bp and 156,554 bp, respectively. The chloroplast genomes of Ceratophyllum encode 113 unique genes, including 79 protein-coding genes, four rRNA genes, and 30 tRNA genes. The assembly of these two chloroplast genomes not only contributes to our understanding of the genome of Ceratophyllum but also provides valuable insights for the evolutionary study of angiosperms.